The Importance and Challenges Of The Islamic Management in Organizational Practice - Zahra, Monica Kis Al; Wiranatakusuma, Dimas Bagus; Aprizal, Anggi (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
For Muslims, Islamic management is an important part of organizational practice. This article aims to identify the importance of involvement of Islamic management and to reveal students’ thought about Islamic management. This study uses a qualitative approach because the researcher wants to obtain deeper answers of each participant. In addition, a semi-structural interview was also conducted by the researcher in order to gather information about the participants’ opinion on Islamic values in organizational practice. The research findings show that Islamic management is impactful in the existence of halal market. However, there some participants who argued that the fact of general management is relatively easier to implement is already a challenge for students to learn Islamic management despite its importance in the organization itself. The expansion of Islamic management knowledge and understanding for students can overcome, there are challenges discussed previously. By looking at findings, it needs the real practical implications and use large scale for further researcher so that they can get more varied data.